Pendampingan dalam Penyuluhan Parenting bagi Wali Murid: Mendidik Anak Usia Golden Age di Era Digital - Farida Isroani (Assoeltan: Indonesian Journal of Community Research and Engagement, 2023)
The digital era is a time that cannot be separated from the rapid increase in information technology. The nature and character of Islam are very valuable as a channel and barrier for children in managing information technology in the current digital era. This is what underlies the importance of Parenting Skills Training. In the Digital Era, the Islamic Digital Parenting community group movement program. This service aims to provide preparatory skills and knowledge to guardians regarding correct Islamic parenting patterns for children in old age. This service activity applies the Participatory Action Research (PAR) method with a participatory approach. This approach provides learning to the community or institutions in overcoming various problems. The results of this activity can stimulate parents and teachers to create learning situations appropriate to the child's developmental age that can be applied in everyday life. So, the implementation of parenting counseling activities on the topic of parenting styles and problem-solving strategies can run smoothly. This parenting activity can be carried out again systematically and sustainably with the hope that the parents of students can continue to update their knowledge, especially in this digital parenting era.